(untitled) (Journal of Engineering, 2007)
The effective stress method is developed to predict the axial capacity of piles in clay. This method is based on the principle that, at failure, the available shear resistance at the pile soil interface is related to the mean normal effective stress at the pile face and the effective stress friction angle for the soil sliding on the pile material. In this paper, the coupled non-linear finite element method is used to analyze some pile-soil interaction problems. This computer program ( CRISP ) is used for this task. Eight- node isoparametric elements were used for displacements while four- node elements are used for pore pressure. Interface elements are used to simulate the interaction between the pile and the soil. The soil is assumed to follow different models, linear elastic and modified Cam-clay model. A comparison is made between the measured and predicted settlements and excess pore water pressures and good convergence was obtained in which the proposed technique used in this paper, in which the measured excess pore water pressures are considered as initial pore pressures in the computer program ( CRISP ). No load was applied on the pile. The dissipation of excess pore water was studied through carrying out consolidation analysis.